Fostering students' participation in creating educational content through crowdsourcing. Issue 1 (2nd January 2019) - Zahirović Suhonjić, Anida; Despotović-Zrakić, Marijana; Labus, Aleksandra; Bogdanović, Zorica; Barać, Dušan
ABSTRACT: This paper proposes and evaluates a model of crowdsourcing in microlearning that includes the balancing of collaborative learning and crowdsourcing mechanisms. The goal of the research is to implement a learner-centered approach through crowdsourced content creation and to improve the process and outcomes of learning. Crowdsourced content creation was accomplished through a collaborative project within a higher education institution. Micro-courses in the form of short video lessons were created by students and published on the Coursmos platform and a certain group of students attended these micro-courses. The evaluation was carried out at the Faculty of Organizational Sciences, the University of Belgrade on a sample of 71 students who created micro-courses and 74 students who attended these micro-courses. The results show that the developed model provides simple communication and collaboration among students, high level of their self-organization and satisfaction, efficient management of crowdsourcing network and collaborative knowledge building.